2008
DOI: 10.1038/ncpneph0830
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of influenza vaccination in renal transplant recipients

Abstract: This Practice Point commentary discusses Scharpé et al.'s single-center, nonrandomized, prospective trial of influenza vaccination in renal transplant recipients. In total, 165 transplant recipients and 41 healthy volunteers were vaccinated with a standard inactivated trivalent influenza vaccine (containing strains of the A/H1N1, A/H3N2 and B viruses). No rejection episodes or other adverse events were reported in either group. Influenza-specific antibody titers increased in renal transplant recipients followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…This review found no increased risk of DSA development, rejection, or graft failure among vaccinated patients. These studies support the safety and efficacy of vaccination in transplant populations (178,187).…”
Section: Vaccinationsupporting
confidence: 70%
“…This review found no increased risk of DSA development, rejection, or graft failure among vaccinated patients. These studies support the safety and efficacy of vaccination in transplant populations (178,187).…”
Section: Vaccinationsupporting
confidence: 70%
“…Although it was uncertain whether vaccination would protect agammaglobulinaemic or hypogammaglobulinaemic patients, they were recommended for pH1N1 mass vaccination in Norway. This decision was made based on previous experience with inactivated influenza vaccines, which are considered safe, also for use in immunocompromised patients [19–21]. The pH1N1 vaccine formulation consisted of an H1N1 split virus vaccine (X179a) formulated with the oil‐in‐water adjuvant AS03 (GlaxoSmithKline, Belgium).…”
Section: Introductionmentioning
confidence: 99%